Epigenetic Regulation in Wilms Tumor - Annabelle Bolitho; Hongbing Liu (Biomedicines)
Wilms tumor (nephroblastoma), the most common pediatric renal malignancy, has a complex genetic and epigenetic landscape. While mutations in genes like WT1, CTNNB1, and WTX have been well characterized, accumulating evidence suggests that epigenetic dysregulation plays a pivotal role in WT pathogenesis. This review examines the various epigenetic mechanisms implicated in WT, including DNA methylation, histone modifications, chromatin remodeling, and non-coding RNA-mediated regulation. We discuss how epigenetic mechanisms contribute to tumor initiation, progression, and heterogeneity and their implications for improved diagnosis and targeted therapy. We also highlight recent advances in epigenomic profiling, discuss the interplay between epigenetics and developmental gene expression programs, and evaluate potential therapeutic strategies targeting epigenetic regulators.